2016
DOI: 10.1016/j.jaridenv.2015.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Climate change effects on southern California deserts

Abstract: Climate change has already affected southern California where regional increases in temperature and vegetation shifts have been observed. While all the CMIP5 temperature projections agree on a substantial level of warming throughout the year, there is fair bit of divergence in the magnitude and seasonality of projected changes in rainfall. While desert plants and animals are generally adapted to extreme conditions, some species may be approaching their physiological threshold. We calculated the climate velocit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 44 publications
1
36
0
Order By: Relevance
“…Similar to our results, Sadoti et al (2017) reported higher probability of movement with increasing NDVI and lower probability of tortoise movement during the highest monthly maximum temperatures. Maximum temperatures of the warmest months in the Mojave Desert are projected to increase approximately 2-3°C in the 21st century (Bachelet et al 2016). Although hotter temperatures during these months will likely restrict desert tortoise movements in the future, projected but variable increases in summer precipitation could mitigate the influence of hotter temperatures on such movements, and associated uncertainty in vegetation productivity will also make it difficult to predict how changes in NDVI will restrict or promote movement (Bachelet et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to our results, Sadoti et al (2017) reported higher probability of movement with increasing NDVI and lower probability of tortoise movement during the highest monthly maximum temperatures. Maximum temperatures of the warmest months in the Mojave Desert are projected to increase approximately 2-3°C in the 21st century (Bachelet et al 2016). Although hotter temperatures during these months will likely restrict desert tortoise movements in the future, projected but variable increases in summer precipitation could mitigate the influence of hotter temperatures on such movements, and associated uncertainty in vegetation productivity will also make it difficult to predict how changes in NDVI will restrict or promote movement (Bachelet et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Maximum temperatures of the warmest months in the Mojave Desert are projected to increase approximately 2-3°C in the 21st century (Bachelet et al 2016). Although hotter temperatures during these months will likely restrict desert tortoise movements in the future, projected but variable increases in summer precipitation could mitigate the influence of hotter temperatures on such movements, and associated uncertainty in vegetation productivity will also make it difficult to predict how changes in NDVI will restrict or promote movement (Bachelet et al 2016). Thus, future research should aim to model Mojave desert tortoise connectivity under a range of projected climate and vegetation scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…Daily mean temperatures of the Mojave Desert are projected to increase approximately 2–3°C in the 21st century (Bachelet, Ferschweiler, Sheehan, & Strittholt, ). Climate models show poorer agreement in projecting precipitation, but tend to project either wetter winters (January–February) or summers (July–August; Rupp, Abatzoglou, Hegewisch, & Mote, ).…”
Section: Discussionmentioning
confidence: 99%
“…Deserts are highly distinct ecosystems that contribute significantly to global biodiversity and global ecosystem function. The conversion and loss of desert habitat is therefore a global biodiversity crisis requiring immediate intervention, including conservation of remaining undisturbed habitat and restoration of degraded desert (Bachelet, Ferschweiler, Sheehan, & Strittholt, ; Cook, ; Hannah, Carr, & Lankerani, ; Hoekstra, Boucher, Ricketts, & Roberts, ; Kéfi et al, ; Mouat & Lancaster, ; Westphal, Stewart, Tennant, Butterfield, & Sinervo, ). Identifying the drivers of ecological health in desert communities will be a crucial component of such interventions.…”
Section: Introductionmentioning
confidence: 99%